Transformation of Cultural Values ​​in Minang-Mandailing Marriage: An Anthropological Study of Islamic Law in West Pasaman Society - Puji Kurniawan; Ahmatnijar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the transformation of cultural values in Minang-Mandailing marriage with the Anthropology approach of Islamic Law in the West Pasaman community. Marriage in the Minang-Mandailing community is not just a social bond, but also a manifestation of customary cultural values that interact with the principles of Islamic law. The West Pasaman community, which consists of various ethnic groups, shows a combination of customary law and Islamic law in the practice of marriage. The research method used is a qualitative approach with case studies in several villages in West Pasaman, which involves in-depth interviews with traditional leaders, religious leaders, and local communities. The results of the study show that there are changes in the implementation of marriage that are influenced by modernization factors, education, and the influence of state law, but still maintain traditional values that are closely related to family honor and social status. On the other hand, Islamic law provides a more egalitarian framework in the rights and obligations of couples in marriage. This transformation of cultural values is also reflected in efforts to harmonize the principles of customary law and Islamic law, which are sometimes conflicting but also complementary. This research is expected to provide insight into the dynamics of the relationship between customary law and Islamic law in the practice of marriage as well as its contribution to social change in the West Pasaman community.